2021
DOI: 10.2196/27463
|View full text |Cite
|
Sign up to set email alerts
|

CANreduce 2.0 Adherence-Focused Guidance for Internet Self-Help Among Cannabis Users: Three-Arm Randomized Controlled Trial

Abstract: Background Despite increasing demand for treatment among cannabis users in many countries, most users are not in treatment. Internet-based self-help offers an alternative for those hesitant to seek face-to-face therapy, though low effectiveness and adherence issues often arise. Objective Through adherence-focused guidance enhancement, we aimed to increase adherence to and the effectiveness of internet-based self-help among cannabis users. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(48 citation statements)
references
References 60 publications
(74 reference statements)
2
44
2
Order By: Relevance
“…In line with previous findings ( Amann et al, 2018 ), some participants missed human interaction. Future studies may complement this intervention with social support, or guidance teams found effective in previous online interventions ( Baumgartner et al, 2021 ; Zarski et al, 2016 ). The suggested changes for improving Hands-off may increase its potential effectiveness in future studies, and the findings extended our insights in designing effective online interventions for PPU in general.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous findings ( Amann et al, 2018 ), some participants missed human interaction. Future studies may complement this intervention with social support, or guidance teams found effective in previous online interventions ( Baumgartner et al, 2021 ; Zarski et al, 2016 ). The suggested changes for improving Hands-off may increase its potential effectiveness in future studies, and the findings extended our insights in designing effective online interventions for PPU in general.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted secondary analysis of the CANreduce 2.0 data set [ 33 ]. The sample was extracted from the 2 active intervention arms (n=367), excluding all individuals in the internet-as-usual group because the study’s purpose was not to determine whether either active intervention was effective relative to a control condition but to compare the degree of effect in patients screening positive versus screening negative for attention deficit/hyperactivity disorder.…”
Section: Methodsmentioning
confidence: 99%
“…The social presence included an eCoach for supportive accountability and human support to enhance adherence to the eHealth intervention. We found moderate to medium effects in the reduction of cannabis use days and significant effects influencing secondary cannabis related outcomes, as well as reducing general anxiety disorder symptoms, when compared to an internet-as-usual control group [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Randomized clinical trial (RCT) results were published in 2015, demonstrating CANreduce to be effective, though beset by an adherence rate that might be improved by creating internet-based applications responsive to all devices (phones, tablets, computers) and adding psychological support [ 24 ]. An updated, adherence-focused guidance enhanced version, CANreduce 2.0, has since been developed [ 25 ] and found to be effective [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the current study, CANreduce 2.0 (an adherence-focused, guidance-enhanced, web-based self-help tool) [ 26 ] was translated into Spanish (CANreduce-SP) and its effectiveness with versus without psychological support compared, in terms of reducing cannabis use among problematic users. Adding psychological support (the option for program users to contact an e-coach to resolve doubts or any concerns they have regarding the program or process) is expected to optimize both adherence to and the effectiveness of the program.…”
Section: Introductionmentioning
confidence: 99%